A Case study on child labor in small-scale mining - Felipe, Catherine N.
This is a study entitled ? a Case study on child laborers in small-scale mining?. This study aims to provide a description of the work conditions of child laborers. The findings are based on face-to-face interview that were conducted in Monte de Oro, Barangay New Barili, Maco, Compostela Valley with children aged 10-16 years old. Guide questions in genera; comprised of open-ended questions about the children's work conditions to gain substantial information relevant for the research. This study is guided by the structuration theory of Giddens on the interplay of the agency and structure in society in affecting the children's decision. A child is a person below the age of 18 years. Child labor is defined as the participation of children in a wide variety of work situations, on a more or less regular basis to earn a livelihood for themselves or for others. The findings revealed that children aged 10-16 years old participate in the small-scale mining activities. Children are involved in the extraction, transportation and processing of minerals. Five of the children are full time workers and one of them works only in the afternoon. Children who are underground workers are assigned to work in narrow tunnels where they dig minerals in uncomfortable positions and without enough ventilation. Children who carry and transport ore carry sacks of mined soil/rock on their backs. Children who are involved in the processing of minerals do not use any kind of protection while in direct contact with mercury. Half of the earnings of child laborers went to their mother, to buy food and other basic needs of the family. Small-scale mining is the prime source of livelihood in Monte de Oro wherein child laborers work for subsistence. They work to support the family's income. These children who work do not attend school and most of them had quited school. The mining area has no health centers. Children also have not received any services/projects for their health and safety from the local government. From the work condition of children, it can be said that it fits the definition of 'child labor', wherein they work under conditions that are considered hazardous to their health and physical well being. As a child they have the right to be informed about their situation, as a child they should be protected from all types of work that can harm their physical and mental well being. Although children perceived their work as normal but still laws and regulations should be implemented in the area to protect these children from any hazards. As a child, they should be enjoying with other children at their age. These children should be going to school, to acquire the necessary knowledge for their full development as humans.